Improving Maternity Care Quality in Nampula, Mozambique: An Implementation Research - Pires, Paulo; Mupueleque, Martins Abudo; Mucufo, Jaibo Rassul; Zakus, David; Siemens, Ronald; Belo, Celso (Disease and Health Research: New Insights Vol. 7, 2024)
Background: Maternity care is an important indicator of national health systems, and the quality of maternity services is an essential factor in reducing maternal and newborn morbidity and mortality, which remains extremely high in Africa. Maternal and child mortality have their highest incidence around delivery time. In Mozambique, the maternal mortality rate was 451.6 deaths per 100,000 live births (2017). The reasons for this are complex, but one important factor in reducing this burden is to provide effective and efficient care, to improve institutional deliveries. To reduce maternal and new-born mortality rates in Nampula, researchers from Lúrio University and the University of Saskatchewan, carried out an implementation research program, including different interventions such as training activities for health professionals in maternal and child health care, information campaigns through radio, theatre and meetings, and transport for deliveries in maternity. A mid-project evaluation was planned to assess the training’s impact on the quality of services at Marrere Hospital Maternity. Methods: Quantitative pre-post study, carrying out two cross-sectional surveys about maternity service quality, one being conducted after five health professionals’ training and the other after six more training. The two surveys included samples of post-partum women in maternity, calculated with a 10% margin error and 90% confidence interval for the first survey, and with a 7% margin error and 95% confidence interval for the second. The surveys were entered into REDCap and analysed to assess frequencies, percentages, means, and standard deviations. This research was approved by the Institutional Committees of Bioethics at Lúrio University and at the University of Saskatchewan. Results: 116 post-partum women were surveyed at the maternity, assessing standards of patient-centred care during delivery labour. Most areas showed no improvement. Some positive improvements were delivering women were given the option to have a person of their choice accompany them during labour (75%), notably a traditional birth attendant (34%), and they had continuous support from a health professional (68%). But many shortcomings persisted in areas of privacy (33%) and confidentiality (57%). Discussion: Health professionals informed delivering women that they had the option to have a person of their choice to accompany them during labour, and this is a low-cost and effective intervention to improve the quality of maternity care, in a context where Traditional Birth Attendants are pregnant women’s trusted partners. Most post-partum women in maternity were satisfied with the service, perhaps due to their low education level leading to lower expectations, since health professionals did not generally proceed according to the rules of good care. This finding might be related to the high turnover of mother and child health professionals, by a mandated reduction of those professionals with an overload of work to those remaining, associated with a hospital’s economic resources reduction, in parallel with low salaries and missing payments for extra-hours. Conclusion: The quality of patient-centred care at Marrere Hospital Maternity did not improve much with health professionals’ training. Decreasing the large turnover rate of such staff, reviewing their learning styles, and promoting continuous professional capacity building would be the next steps to improve the quality of care. These policy developments could significantly better mother and child health at Mozambican health centres and hospitals.